New Players in Metabolic Syndrome - Iveta Nedeva; Yavor Assyov; Vera Karamfilova; Zdravko Kamenov; Pavel Dobrev; Tsvetelina Velikova; Vlayko Vodenicharov (Metabolites, 2025)
Background/Objectives: Metabolic syndrome (MetS) is a complex, multifaceted disorder with significant socioeconomic and public health consequences, increasingly acknowledged as a global epidemic. Fibroblast growth factor 21 (FGF-21) is known to play a vital role in metabolic regulation; however, the precise roles and interactions of free fatty acids (FFAs) and insulin in influencing FGF-21 activity under both normal and pathological conditions are not yet fully understood. Meteorin-like protein (Metrnl) is a newly identified adipokine that appears to have the potential to regulate metabolic inflammation, which is a critical pathological factor in obesity and insulin resistance. Additionally, nesfatin-1, which is widely expressed in both central and peripheral tissues, is thought to be involved in various physiological functions beyond appetite control, such as glucose homeostasis, stress response, and cardiovascular health. Recent studies have indicated that sortilin may play a role in the pathophysiology of several metabolic disorders, including type 2 diabetes mellitus. Methods: This investigation was a cross-sectional study involving 200 individuals with obesity, which included both metabolically healthy obese participants and those experiencing obesity along with glycemic disorders. Serum levels of FGF-21, sortilin, Metrnl, and nesfatin-1 were measured using standardized enzyme-linked immunosorbent assay (ELISA) techniques. Results: The results indicated that FGF-21 levels were significantly elevated in patients with metabolic syndrome (p < 0.001), as well as those with insulin resistance (p = 0.009) and dyslipidemia (p = 0.03). Serum Metrnl levels were notably elevated in individuals meeting the criteria for insulin resistance, with a statistical significance of p < 0.001. Additionally, patients experiencing carbohydrate metabolism disorders exhibited significantly higher serum sortilin levels compared to those with normal blood glucose levels, with a p-value of 0.003. Conclusions: This research highlights FGF-21, Metrnl, nesfatin-1, and sortilin as potential biomarkers involved in the development of critical aspects of metabolic syndrome.